x-y=6

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract x from both sides of the equation.

-y=6-x

Multiply each term in -y=6-x by -1

Multiply each term in -y=6-x by -1.

(-y)⋅-1=6⋅-1+(-x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=6⋅-1+(-x)⋅-1

Multiply y by 1.

y=6⋅-1+(-x)⋅-1

y=6⋅-1+(-x)⋅-1

Simplify 6⋅-1+(-x)⋅-1.

Simplify each term.

Multiply 6 by -1.

y=-6+(-x)⋅-1

Multiply (-x)⋅-1.

Multiply -1 by -1.

y=-6+1x

Multiply x by 1.

y=-6+x

y=-6+x

y=-6+x

Reorder -6 and x.

y=x-6

y=x-6

y=x-6

y=x-6

Find the values of m and b using the form y=mx+b.

m=1

b=-6

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: 1

y-intercept: -6

Slope: 1

y-intercept: -6

Find the Slope and Y-Intercept x-y=6